Extrapleural pneumonectomy of recurrent thymoma with pleural dissemination. Issue 4 (28th February 2018) - Shiiya, Haruhiko; Hida, Yasuhiro; Kaga, Kichizo; Inoue, Rei; Nakada‐Kubota, Reiko; Matsui, Yoshiro
Abstract : The safety and efficacy of extrapleural pneumonectomy for recurrent, disseminated thymoma has been controversial. We report a good outcome of young fit patient after extrapleural pneumonectomy. Abstract : Complete surgical resection has been considered the only curable treatment for thymoma. The efficacy of extrapleural pneumonectomy (EPP) for stage IV thymomas remains controversial. In this case report, we utilize EPP for recurrent thymoma with pleural dissemination and describe the resulting outcome. A 39‐year‐old female with a history of thoracoscopic thymectomy for type B2 thymoma was referred to our hospital for a recurrence of thymoma with pleural dissemination. She underwent EPP as a radical surgery. Histopathological investigation revealed complete resection. The postoperative course was uneventful. She returned to her full‐time job and showed no sign of recurrence at 31 months after surgery. EPP for recurrent thymoma with pleural dissemination may be considered to achieve macroscopically complete resection when the patient is young and has a sufficient pulmonary function reservoir without preoperative complications.